« Envoyer la maladie ». Entre sorcellerie et politique, l’évolution des conceptions du sida dans les zones rurales d’Haïti [1990] - Paul Farmer (Genre, Sexualité et Société)
In this article I trace the emergence of a collective representation of AIDS in a village in rural Haiti. I initiated investigation of local understandings of AIDS years before the advent of the illness to the community itself and continued documenting the subsequent elaboration of a fairly detailed and widely shared cultural model of the new disorder. Through following serial interviews with the same persons over a period of six years, one can discern the rate at which consensus was achieved, the events which led to it, and the significance of preexisting interpretive frameworks for current understandings of AIDS. This case contributes to the anthropological study of cultural meaning in formation and transformation.